Understanding financial statements : a primer of useful information - Gill, James O. (Crisp Pub. Menlo ParkUS, 1990)
Explains fundamental concepts of basic financial analysis such as: what a balance sheet, and a profit and loss statement really show. Provides glossaries of balance sheet terms, and profit and loss statement terms. Presents the liquidity, profitability and efficiency ratios, and explains how to use them to measure and control a business.